2019
DOI: 10.18632/oncotarget.26582
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of ATM kinase upregulates levels of cell death induced by cannabidiol and γ-irradiation in human glioblastoma cells

Abstract: Despite advances in glioblastoma (GBM) therapy, prognosis of the disease remains poor with a low survival rate. Cannabidiol (CBD) can induce cell death and enhance radiosensitivity of GBM but not normal astrocytes. Inhibition of ATM kinase is an alternative mechanism for radiosensitization of cancer cells. In this study, we increased the cytotoxic effects of the combination of CBD and γ-irradiation in GBM cells through additional inhibition of ATM kinase with KU60019, a small molecule inhibitor of ATM kinase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 82 publications
1
23
0
Order By: Relevance
“…We additionally used ATM inhibitor (ATMi) KU60019 35 , alone or in combination with γ-irradiation and CBD, to investigate its downstream effects on autophagy. We previously confirmed specificity of ATM kinase inhibitor (ATMi) KU60019 (at concentration 1-2 μM) for suppression γ-irradiation-induced ATM activation in U87MG cells 31 . Interestingly, the presence of ATMi (1-2 μM) in non-irradiated or, especially, in γ-irradiated GBM cells was linked with upregulation of LC3-II levels 24-48 h after treatment ( Fig.…”
Section: Cbd-mediated Upregulation Of Autophagy In a 2d Culture Of U8supporting
confidence: 57%
See 4 more Smart Citations
“…We additionally used ATM inhibitor (ATMi) KU60019 35 , alone or in combination with γ-irradiation and CBD, to investigate its downstream effects on autophagy. We previously confirmed specificity of ATM kinase inhibitor (ATMi) KU60019 (at concentration 1-2 μM) for suppression γ-irradiation-induced ATM activation in U87MG cells 31 . Interestingly, the presence of ATMi (1-2 μM) in non-irradiated or, especially, in γ-irradiated GBM cells was linked with upregulation of LC3-II levels 24-48 h after treatment ( Fig.…”
Section: Cbd-mediated Upregulation Of Autophagy In a 2d Culture Of U8supporting
confidence: 57%
“…Additional investigations also confirmed a cytotoxic role of cannabinoids for several other types of cancer 12,30,51 . A number of studies demonstrated the efficiency of combined treatments of cannabinoids together with γ-irradiation in both cell culture and in animal experiments 17,18,28,31 . CBD treatment can induce apoptotic death in GBM using both the intrinsic and extrinsic death pathways 52 while γ-irradiation results in enhancing apoptotic and non-apoptotic cell death, especially in the presence of ATM inhibitor 31,53 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations